(untitled) (Journal of Organizational Psychology, 2020)
We developed and tested a model examining the influence of employee well-being on reported levels of affective organizational commitment. Utilizing the PERMA profiler to measure positive emotion, negative emotion, and physical health, we proposed that positive emotion and physical health increase affective commitment levels. Subsequently, we assess whether negative emotion and ill-physical health decrease reported affective commitment. We tested our model utilizing 190 respondents taken from an anonymous survey. Findings support our hypotheses as high levels of positive emotion and physical health positively impact affective commitment. Negative emotion and physical ill-health, on the other hand, decrease employee affective commitment.